KONFLIK SOSIAL KASUS TEGAL DAN CILACAP - Fathoni Moehtadi (Sosio Informa, 2003)
Phenomenon of conflict is a part of social life. Latent and manifest conflict should be seen as of social dynamic. From several social disturbance that happened have been identified that the trigger was not the main cause. It was only cases belli and as accumulation of latent conflict. The main causes may can be identified by accurate study within certain time.